Dielectric properties of thin films of Babassu-based polymer and polyaniline blends - da Cunha, Giovanni P.; de Matos Borges, Fernando; Dognani, Guilherme [UNESP]; Bacarin, Giovani B. [UNESP]; Cabrera, Flávio C. [UNESP]; Job, Aldo E. [UNESP]; Matos, José Milton E.; Vega, Maria Letícia; da Cunha, Helder N. (Wiley, 2018)
In the present work, we describe the preparation and subsequent characterization of polymeric blends consisting of a monoglyceride (MG) synthesized from the Babassu's oil and the already commonly employed polyaniline (PAni). By following changes in the complex impedance of capacitor-like devices we observe that the presence of MG in the PAni/MG blends decreases electrical conductivity and that this decrease is a function of the content of MG in the blend, i.e., the blend with 30% of MG shows Z′ about seven times greater than the one with 10% of MG. Fourier transform infrared measurements prove the formation of MG and the presence of secondary amine groups (NH bonds) in the blends, which allow for the chemical doping of PAni by protonation, further studies are necessary to access the viability of employing this new material as active layer in electronic organic devices. Atomic force microscopy images show the formation of agglomerates due to the presence of MG. In addition, the polymeric mixture acts only as a blend, providing a physical interaction between different components. © 2018 Wiley Periodicals, Inc. J. Appl. Polym. Sci. 2018, 135, 46198.
Keywords: applications; blends; conducting polymers